Recommendations for Diagnosis and Treatment of Odontoid Fractures in Geriatric Patients - Osterhoff, Georg; Schnake, Klaus; Scheyerer, Max J.; Ullrich, Bernhard W.; Hartmann, Frank; Franck, Alexander; Koepp, Holger; Reinhold, Maximilian; Schmeiser, Gregor; Sprengel, Kai; Zimmermann, Volker; Siekmann, Holger; Badke, Andreas; Gebhard, Harry; Täubel, Kai C.; Grüninger, Sebastian; Verheyden, Akhil P.; Schleicher, Philipp; Spiegl, Ulrich J. A.; AG „Obere Halswirbelsäule“ und AG „Osteoporotische Frakturen“ der Sektion Wirbelsäule der Deutschen Gesellschaft für Orthopädie und Unfallchirurgie (Zeitschrift für Orthopädie und Unfallchirurgie, 2019)
Background Odontoid fractures in geriatric patients represent an entity of increasing incidence with a high rate of morbidity and mortality. The optimal diagnostic and therapeutic management is being controversially discussed in the literature.Methods In a consensus process and based on the current literature, the members of the working groups “Osteoporotic Fractures” and “Upper Cervical Spine” of the German Society for Orthopaedics and Trauma Surgery (DGOU) defined recommendations for the diagnostics and treatment of odontoid fractures in geriatric patients.Results For the diagnosis of odontoid fractures in symptomatic patients, computed tomography represents the gold standard, along with conventional radiographs. Magnetic resonance and dynamic imaging can be used as ancillary imaging modalities. With regard to fracture classification, the systems described by Anderson/DʼAlonzo and by Eysel/Roosen have proved to be of value. A treatment algorithm was developed based on these classifications. Anderson/DʼAlonzo type 1, type 3, and non-displaced type 2 fractures usually can be treated non-operatively. However, a close clinical and radiological follow-up is essential. In Anderson/DʼAlonzo type 2 fractures, operative treatment is associated with better fracture healing. Displaced type 2 and type 3 fractures should be stabilized operatively. Type 2 fractures with suitable fracture patterns (Eysel/Roosen 2A/B) can be stabilized anteriorly. Posterior C I/II-stabilization procedures are well established and suitable for all fracture patterns.Hintergrund Frakturen des Dens axis beim geriatrischen Patienten stellen eine wachsende Entität mit hoher Morbidität und Mortalität dar. Die optimale Diagnostik und Behandlung der Verletzung in diesem Patientenkollektiv werden in der Literatur kontrovers diskutiert.Methodik In einem gemeinsamen Konsensusprozess erstellten die Mitglieder der Arbeitsgemeinschaft „Osteoporotische Frakturen“ und der Arbeitsgemeinschaft „Obere Halswirbelsäule“ der Sektion Wirbelsäule der Deutschen Gesellschaft für Orthopädie und Unfallchirurgie (DGOU) unter Berücksichtigung aktueller Literatur Empfehlungen zu Diagnostik und Behandlung von Frakturen des Dens axis bei geriatrischen Patienten.Ergebnisse In der Diagnostik der Densfrakturen stellt beim symptomatischen Patienten neben der konventionellen Bildgebung die Computertomografie den Goldstandard dar. Kernspintomografie und Funktionsaufnahmen können ergänzende Informationen liefern. Zur Klassifikation haben sich die Systeme nach Anderson/DʼAlonzo und Eysel/Roosen bewährt. Anhand der genannten Klassifikationen wurde ein Behandlungsalgorithmus entwickelt: Anderson/DʼAlonzo Typ 1, Typ 3 und nicht dislozierte Frakturen vom Typ 2 können i. d. R. unter engmaschigen Verlaufskontrollen konservativ behandelt werden. Bei Frakturen vom Typ 2 nach Anderson/DʼAlonzo bietet die operative Behandlung den Vorteil höherer knöcherner Heilungsraten. Dislozierte Typ-2- und Typ-3-Frakturen sollten operativ stabilisiert werden. Bei geeignetem Frakturverlauf (Eysel/Roosen 2A/B) sind anteriore Verfahren möglich. Posteriore Verfahren zur C I/II-Stabilisation sind etabliert und bei allen Frakturtypen durchführbar.
Keywords: odontoid fracture; dens axis; osteoporosis; osteoporotic fracture; cervical spine